2018
DOI: 10.1111/jsap.12948
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia of brachycephalic dogs

Abstract: Brachycephalic breeds of dog have grown in popularity in the UK and so form an increasing proportion of cases requiring anaesthesia. These breeds are predisposed to several conditions, notably brachycephalic obstructive airway syndrome and gastro‐oesophageal reflux, that have important implications for anaesthetic management and carry high risk for complications. This review incorporates peer‐reviewed veterinary literature with clinical experience in a discussion on perioperative management of brachycephalic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 71 publications
0
61
0
4
Order By: Relevance
“…We believe widespread use of omeprazole and maropitant in brachycephalic dogs has been related to a previous study that concluded "medical treatment of upper GI disorders [using omeprazole and the prokinetic cisapride]… dramatically improves the prognosis following surgical treatment of brachycephalic obstructive airway disease" 38 : this conclusion has been repeated subsequently by others 39 . However, this study was a prospective case series, meaning that such conclusions could not be drawn in the absence of a control group.…”
Section: Discussionmentioning
confidence: 79%
“…We believe widespread use of omeprazole and maropitant in brachycephalic dogs has been related to a previous study that concluded "medical treatment of upper GI disorders [using omeprazole and the prokinetic cisapride]… dramatically improves the prognosis following surgical treatment of brachycephalic obstructive airway disease" 38 : this conclusion has been repeated subsequently by others 39 . However, this study was a prospective case series, meaning that such conclusions could not be drawn in the absence of a control group.…”
Section: Discussionmentioning
confidence: 79%
“…A limitation of the studies evaluated is the inclusion of all breeds. Brachycephalic breeds are more susceptible to GOR due to the increase in negative intrathoracic pressure as a result of overcoming upper respiratory tract obstruction associated with brachycephalic obstructive airway syndrome (Downing and Gibson, 2018). Therefore, the inclusion of brachycephalic breeds, which is unknown in these studies may bias the results.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
“…Os efeitos antieméticos das fenotiazinas são benéfi cos em tais associações (PAWSON, 2010; RANKIN, 2015). O principal fármaco dessa classe empregados em pequenos animais é a acepromazina RANKIN, 2015;MURREL, 2016;DOWING & GIBSON, 2018), sua dose para cães é de 0,01 a 0,1 mg/kg, pelas vias intravenosa, intramuscular ou subcutânea. O tempo para aparecimento do efeito total é de aproximadamente 30 minutos após as injeções intramusculares, mas é menor se utilizada a via intravenosa .…”
Section: Fenotiazínicosunclassified
“…jejum pré-anestésico é sempre pré-requisito para um procedimento eletivo, devido à existência de conteúdo gástrico que eleva o perigo de regurgitação no decorrer da anestesia injetável e/ou após o procedimento, sendo capaz de ocorrer aspiração via traqueal e, por consequência, o desenvolvimento de um possível quadro de pneumonia por aspiração. O recomendado é jejum alimentar de 12 horas e hídrico de duas horas, sendo que braquicefálicos possuem maior propensão a regurgitação se possuírem edema de epiglote(DOWING & GIBSON, 2018).…”
unclassified